Post-acute COVID-19 syndrome in patients after 12 months from COVID-19 infection in Korea - Kim, Yoonjung; Bitna-Ha; Kim, Shin-Woo; Chang, Hyun-Ha; Kwon, Ki Tae; Bae, Sohyun; Hwang, Soyoon (BMC infectious diseases, 2022)
Background As the coronavirus disease 2019 (COVID-19) pandemic continues to progress, awareness about its long-term impacts has been growing. To date, studies on the long-term course of symptoms, factors associated with persistent symptoms, and quality of life after 12 months since recovery from acute COVID-19 have been limited. Methods A prospective online survey (First: September 8, 2020–September 10, 2020; Second: May 26, 2021–June 1, 2021) was conducted on recovered patients who were previously diagnosed with COVID-19 between February 13, 2020 and March 13, 2020 at Kyungpook National University Hospital. Responders aged between 17 and 70 years were included in the study. Overall, 900 and 241 responders were followed up at 6 and 12 months after recovery from COVID-19 in the first and second surveys, respectively. Clinical characteristics, self-reported persistent symptoms, and EuroQol-5-dimension (EQ5D) index score were investigated for evaluating quality of life. Results The median period from the date of the first symptom onset or COVID-19 diagnosis to the time of the survey was 454 (interquartile range [IQR] 451–458) days. The median age of the responders was 37 (IQR 26.0–51.0) years, and 164 (68.0%) responders were women. Altogether, 11 (4.6%) responders were asymptomatic, and 194 (80.5%), 30 (12.4%), and 6 (2.5%) responders had mild, moderate, and severe illness, respectively. Overall, 127 (52.7%) responders still experienced COVID-19-related persistent symptoms and 12 (5.0%) were receiving outpatient treatment for such symptoms. The main symptoms were difficulty in concentration, cognitive dysfunction, amnesia, depression, fatigue, and anxiety. Considering the EQ5D index scores, only 59.3% of the responders did not have anxiety or depression. Older age, female sex, and disease severity were identified as risk factors for persistent neuropsychiatric symptoms. Conclusion COVID-19-related persistent symptoms improved over time; however, neurological symptoms can last longer than other symptoms. Continuous careful observation of symptom improvement and multidisciplinary integrated research on recovered COVID-19 patients are required.